MEMAKNAI SIKAP INTEGRITAS AKUNTAN PUBLIK DI KAP “CEMERLANG” SURABAYA (STUDI FENOMENOLOGI) - Ratna Anggraini Aripratiwi; Unti Ludigdo; M. Achsin (Universitas Muhammadiyah Malang)
This study aims to explore the deep meaning of integrity attitudes experienced, felt, and run bypublic accountants in one of the famous KAP in Surabaya, KAP “Cemerlang”.Revealing theattitude of the integrity of public accountants because of the many public accountants are stilldragged into fraud and violations, resulting in unethical decisions. Every public accountant hasa different perspective in determining and exercising an attitude of integrity, whether to defendor even take it off for a particular purpose. And in the end bring up a variety of diverse meaningsof pure integrity and pragmatic integrity.Keywords: Integrity, phenomenology, public accountant.